School-Based Education Improvement Initiatives : The Experience and Options for Sri Lanka - World Bank (Washington, DC, 2014)
Most developing countries following independence opted for strong central control and direction of the education system, partly because of limited resources and the need to plan carefully and partly because of a felt need to create a sense of national unity among diverse ethnic and linguistic groups. This meant that key areas of control and decision making, such as management of resources and personnel, curriculum, evaluation of performance, and accountability, were under central rather than local control. The empowerment of schools has two major components: school-based management and the involvement of parents and communities in the work of schools. The emphasis given to one or other of these components depends on general national policy, local traditions, and context, with the result that almost every system is unique when one considers who makes decisions, the actual decisions that are made, the nature of those decisions, the level at which they are made, and relationships between levels. Thus, there are 'strong' and 'weak' versions of school empowerment. In some, only a single area of autonomy is granted to schools, while in others the community management of schools, even the establishment of schools, is encouraged (World Bank, 2007). In this paper, the author will briefly outline the history of school empowerment in Sri Lanka with particular reference to the Program for School Improvement (PSI), which commenced in 2006. The final section of the paper contains suggestions designed to strengthen process of empowering Sri Lankan schools and improving education outcomes.